REVITALISASI OBJEK WISATA RUMAH TENUN PUCUK REBUNG HJ YAHYA KAMPUNG BANDAR KECAMATAN SENAPELAN KOTA PEKANBARU - Rona Sitorus; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine 1. How to Revitalize a Tourist Attraction Rumah Tenun Pucuk Rebung Hj Yahya Kampung Bandar Kecamatan Senapelan Pekanbaru City 2. What are the Obstacles of Revitalization of Objects of Rumah Tenun Pucuk Rebung Of Hj Yahya Kampung Bandar Kecamatan Senapelan Kota Pekanbaru. This research uses qualitative method with descriptive approach, Research subjects are managers Rumah Tenun Pucuk Rebung of Hj Yahya Kampung Bandar Kecamatan Senapelan Kota Pekanbaru. Tour conscious group Local people, Department of Culture and Tourism Pekanbaru City And Visitors. Data collection conducted, thatis by document study, observation, depth interview. Data analysis With data reduction, data presentation, conclusion drawing.The results showed that the revitalization of tourism objects Rumah Tenun Pucuk Rebung Hj Yahya Kampung Bandar Kecamatan Senapelan Pekanbaru City Is still poorly managed due to social and economic aspects. Barriers to revitalization of Objects of Rumah Tenun Pucuk Rebung Of Hj Yahya Kampung Bandar Kecamatan Senapelan Kota Pekanbaru is Environmental conditions located in densely populated areas, surrounding communities who are less concerned about the condition of the House, and No Assistance from the government.Keyword :Revitalization, RumahTenunPucukRebung, Kampung Bandar